Stabilisation of black cotton soils using fly ash, Hubballi-Dharwad Municipal Corporation Area, Karnataka, India (Global Journals of Research in Engineering, 2012)
Urbanisation and growth in the economy of tier-2 cities of India have led to the steep increase in the building construction activities and has necessitated the implementation of infrastructure projects such as highways railways air strips water tanks reclamation etc These projects invariably require quality earth in massive quantity In urban areas borrow earth is not easily available which has to be hauled from a long distance Quite often large areas are covered with highly plastic and expansive soil which is not suitable for such purpose The twin city of Hubballi-Dharwad is a fastest growing tier-2 city of Karnataka state and is the second largest city of the state just next to Bangalore The wide spread of the black cotton soil in the twin city of Hubballi-Dharwad has posed challenges and problems to the construction activities A task was therefore undertaken to investigate and improve the engineering properties of the black cotton soils of Hubballi-Dharwad Municipal Corporation area so that a better understanding is facilitated for the civil engineering practitioners while dealing with these soils
Keywords: Stabilisation of black cotton soils; Fly ash; Hubballi-Dharwad Municipal Corporation; Karnataka; India